Apiaceae across time: A comparative study of medicinal uses from Dioscorides and Ibn Al Baytar to contemporary Northeastern Morocco - Mir, Fatima-Zahra; Smaili, Halima; Merzouki, Abderrahmane (Ethnobotany Research and Applications, 2026)
Background: This study examines how medicinal knowledge related to the Apiaceae family has changed over time. Contemporary ethnobotanical data from Northeastern Morocco (Al Hoceima, Nador, and Jerada) were compared with information found in two historical texts: De Materia Medica by Dioscorides (1st century CE) and the Compendium on Simple Medicaments and Foods by Ibn Al-Baytar (13th century). The aim was to identify which traditional uses have persisted, changed, or disappeared. Methods: Field surveys carried out between 2017 and 2019 involved 1,177 informants. All reported uses were classified according to the ICPC-2 system. The Jaccard Index was used to measure similarity between the three sources, both by species and by groups of diseases. Heatmaps and hierarchical clustering were used to visualize patterns. Results: The results showed that the transmission of medicinal knowledge was uneven. Some groups of diseases, especially digestive disorders (D), show clear continuity between past and present. Other groups displayed very low or zero similarity values, indicating a loss of some practices. At the species level, some taxa showed stable uses across all sources, some retain only part of their former uses, and others show a complete break with historical knowledge. Conclusions: Overall, the study shows that traditional knowledge doesn’t evolve in a uniform way. Some uses persist, others change, and many disappear. Understanding these patterns helps document the history of Moroccan medicinal knowledge and show the importance of preserving ethnobotanical traditions. Keywords: Apiaceae; Dioscorides, Ibn-Al Baytar, Contemporary ethnobotany, Morocco